The Woman’s Silent Voice toward Patriarchy’s Handcuff Reflected in AtiqRahimi’sThe Patience Stone - RIZKI SURYA ADI P (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Abstrak Patriarkiadalah salah satumasalahbesar bagisetiapwanita di dunia, masalah iniakhirnyadiwakilidengankarya sastra, dansalah satunya adalahAtiqRahimiBatuKesabaran.Terdapat Perempuan, sebagai karakter utamadiceritakandengan semuakesedihan, menikahdengan dipaksa, menikahdengan foto, sampai diaharus membuathamil dengantanpajalan dandia memilikibayi daripria laindia tidak pernahtahu. Berdasarkanfakta-fakta, ini memberikan dua pertanyaanutama sebagairespondarimasalah, adalah(1) GambaranbelenggupatriarkimelaluisuaradiamPerempuandiAtiqRahimiBatuKesabaran?(2) DampaksuaradiamPerempuandiAtiqRahimi, BatuKesabaran?Untuk mengatasi hal itudengan analisis, membutuhkanmetode yangmembaca, mengumpulkan data, dan interpretasi, teknik yang digunakanadalahinterpretasi, dan pendekatanmimesis. Sebagaihasil dariini, itu akanmenemukan sesuatu, suaradiamPerempuan, dan initerjadidi Afghanistan, oleh karena itu,dapat dikatakanbahwa sistempatriarkibisa mengambilhak-hak perempuan, dan apahal-hal yangdapat memberikanPerempuanadalahsuaradiam,suarayang dapat menjadigerakan feminisuntuk setiapsimpatiuntuknya. Ini mewakili, untukberkatadalam bisikanyang sangathalus yangmasih adaketimpanganyang disebabkan olehpatriarki, danWanitatidak dapatberbuat apa-apa. Kata Kunci: Patriarki, perempuan, suaradiam, danfeminisme. Abstract Patriarchy is one of the great problem for every women in the world, this problem finally is represented to a literary work, and one of it is AtiqRahimi’sThe Patience Stone. There, the Woman, as the main character is told with all sorrow, marrying by being forced, marrying with a photo, until she has to make pregnant with regardless the way and she has baby from another guy she never knows. Based on the facts, it delivers two main questions as the response of problems, they are (1) Depiction of patriarchy’s handcuffthrough the Woman’s Silent Voicein AtiqRahimi’sThe Patience Stone? (2) The impact ofthe Woman’s Silent Voice in AtiqRahimi’sThe Patience Stone? To solve it by analysis, it requires a method that is reading, collecting data, and interpretation, the used technique is interpretation, and the approach is mimesis. As the result of this, it will find something, the silent voice of the Woman, and this is happen in Afghanistan, therefore, it can be said that patriarchy system can grab the rights of women, and what things that the Woman can deliver is the silent voice, the voice that can be a feminist movement for every sympathy to it. It represents, it says in very smooth whispers that there are still inequality caused by patriarchy, and the Woman cannot do anything. Keywords: Patriarchy, women, silent voice, and feminism. INTRODUCTION Human lives in the world are like corrosion on the ply of metal in the process of abrasion. What the core of this analogy is the way human wear their brain shell to think and find the solution of every problem they face to. Human are divided in to two genders normally, they are men and women. Men, a creature whose penis sticks strongly with dignity and power to dig every hole in front of it. Women, a creature whose vagina decorates beautifully with softness and warmness for everything that prepares for digging it. Based on the differences of the two, the conflicts arise. It starts when women begin realizing that what they think is their right, is grabbed by the creature, called men. In addition, this thought probably can be supposed as the basic thought of feminism movement. Before going further to the meant feminism, it is important to see what feminism fights to, and it is patriarchy system. Patriarchy system is a system that has been rooted in society generally. Erich From asserts that Patriarchy system is where men is fated to dictate/control women, and it rules to all part in the world. (Fromm, 2002: 177). To add it, to make the establishment of this system of men, chronologically there are some experts that give distance between men and women where men are supposed to be the better one. Classically, women are inequality creature, and it is added by Aristotle who views women as an imperfectness of nature (Beauvoir, 2003:ix). Francis Bacon comments that the more negative assertion that women are the jail of men because women give bad effect or influence to men (Arivia, 2002:40). Kant even says that women does not have any ability to use their cognitive ability therefore women should not be allowed to deliver what they think (Arivia, 2002:40). While, St. Thomas supposes women as “imperfect men”, women are creature who are created not deliberately, and it is proven by the symbolic story where Eve is portrayed by Bossuet as a creature who is made of the “Adam’s Rib” (Beauvoir, 2003:xi). According to Cixous, the term of men and women pinpoints to the difference of the two where the first term must posit the higher or better meaning, and it is placed by men. Therefore, men are self and women are the Liyan. Women live in men’s world, therefore women are considered as the Liyan for men. (Tong, 2009: 292). Based on those facts, society finally construct a system where men dominate the whole contents of social life. J. Douglas (1976: 34) adds that many feminists use the term patriarchy as a generic term for male privilege, supremacy, and domination, referring to their current as well as past forms. The attraction of this usage is readily apparent: first, its rhetorical punch and strongly pejorative connotations; second, its reminder of the tenacity and continuity of male domination. Despite earth-shaking social changes, not the least of which are the women's Movements of the nineteenth and twentieth century, male power remains. Therefore, what the things that can be inferred into these facts are the problems between men and women. Feminism moves to throw everything that involves in men’s domination because they dictate women, women seem to live in a coop. It means that what women fight is the system of men. In general, feminism is the theory of women’s liberation since the intrinsic in all its approaches is the belief that women suffer injustice because of women’s sex (Humm, 1989: 74). From the inequality that exists between both gender, women want to search equality in the society, they start to speak up their voices in the publicarena. Women themselves must articulate who they are and what role they play in the society. Most importantly, they must reject the patriarchal assumption that women are inferior to men. This started the feminist movement. It was started by the reality that male-female relations is a form of power structure in which men dominate women (Thebaud, 1994: 290). From this starting point the feminist believe that existing inequalities between dominant and marginalized groups can and should be removed. In the practive the feminist scholars attempt to examine beliefs and practices from the viewpoint of the “other”, in this case women, treating them as subjects, not merely objects. Based on those views, it can be said that feminism simply is a thought that focuses on the equality between men and women, especially to talk about the rights of women. Therefore, what things that can be put into the main topic of this, is the all things relates to the inequality between men and women where men are supposed to be the superiority ones. Feminism itself is part of cultural studies in literature, which arises since women feel discredited and being treated unequal to men as human. Yet, what is not acceptable is the differentiation in position, that men are superior to women. That awareness prompts women to rise up and fight for their rights. Feminism deals with freedom, appreciation, and fair treatment for women. It is not women’s disability to sit equal with men, but the systems in their social life discourage women to gain self-assertion to actualize themselves as well as men. Meanwhile, women want to grow as human beings who have equal role and opportunity in their own life and society. In the West and East alike, feminists were up against home-grown patriarchalist opponents who used sundry means to denigrate feminism and its supporters. In the West, detractors portrayed feminists as man-haters. In the East, enemies branded feminists as agents of cultural subversion and, ironically in so doing ‘colluded’ with westerners in declaring feminism western. (Kynsilehto, 2008: 26). Therefore, what can be integrated from this Islam feminism understanding is the way Islam see the equality between men and women, from the agents of truth about the equality between men and women, not creating women to hate men just to beg an equality as what west feminism says to. It is clear to see that this problem finally inspires some authors to write it down in beautiful work, and one of it is AtiqRahimi with his novel entitled The Patience Stone. The main thing that is hidden in AtiqRahimi’sThe Patience Stone is the way feminism is shown up. This novel, especially the main character, the woman, erodes the feeling of the readers to give sympathy and tears on what has happened to the woman. The woman cannot fight to the system of men he faces on, but she just can deliver it through a telling to her comate husband, which is not changing anything to her fair life. Specifically, in Atiq Rahimi’s The Patience Stone, there is told a woman sits in front of his comate husband. She tells everything she never confesses before because of some reasons. She is the wife of a soldier who is lying unconscious with a bullet in his neck, and she calls her husband with The Patience Stone or “Sang-e Saboor,” it is a mythical stone accords to Persian folklore that absorbs the pain of those who confide in it, until it eventually explodes. When the novel opens, the man has been comatose for over two weeks, and shows no signs of recovery. Frustration and despair on the woman’s part gradually turns to angry rebellion and, uncertain whether or not he can hear her words, she becomes ever more talkative and outgoing as she gathers over their ten-year marriage. The thing that is important to know is that the couple didn’t meet before their wedding, nor even during it, since he was away fighting. Instead a ceremony was performed between the teen bride (the Woman) and a photograph, after which she spent three years as a married virgin. She is not allowed to be out of house of seeing friends and family. When the Husband returns, she discovers that she is married to a violent, because the Husband brutally detaches sex at the first sex time. It can be seen that the woman as main character reflects “handcuff” of women life against patriarchy in the social life of the novel. The Women uses her inability to comprehend and talk back to tell him things that she will not dare to say otherwise. With his disability she has been left to feed herself, her two children and continue buying medicine to keep her husband alive. The only job available for an Afghan woman in her desperate situation it seems is prostitution. It is an interested topic to explore because AtiqRahimi’sThe Patience Stone is part of a Persian myth about a stone that has this phenomenal strength to listen to stories of suffering and sorrow. What sorrow that is delivered is from the heart voice of a woman that lives in the unfair world. The unfair world is caused by the inequality. Thus, to respond it, the readers must have attention to give sympathy to the woman indirectly, and to call this feeling, it is not too naïve when it said as the feminist movement that calls everyone in talking the equality women should have. To classify it, this thought belongs to first wave, where women have voice to utter although it is not a fight directly. Then, the voice that is not changing anything significantly to what the Woman faces, is the silent voice. Silent voice is the voice that is not heard, listened, and sensed. However, this voice exists, and the existence gnaws sympathy to see how unequal the social system the Woman faces, the sympathy that dribbles to feminism thought indirectly to get the equal rights. Based on the reasons above, this thesis then conveys analysis on the life and some aspect of main characters thorough feminism approach accords to patriarchy concepts and understanding in AtiqRahimi’sThe Patience Stone. Finally, the planned title can be written as The Woman’s Silent Voice toward Patriarchy’s Handcuff Reflected in AtiqRahimi’sThe Patience. For more additional support that this thesis uses credible object, it is important to see that AtiqRahimi’sThe Patience Stone is the winner of Prix Goncourt Prize in 2008. Therefore, this thesis hopefully can be a great product and be great donation of literary critics and analysis. Indeed, the decision to select AtiqRahimi’sThe Patience Stone rather than the other works of him is caused by the main topic of the work. AtiqRahimi’s The Patience Stone delivers more complex problem between men and women, that finally grabs the problem of Patriarchy and Feminism, while the feminism that is used is based on the glasses of Islam because the setting is in Afghan. In AtiqRahimi’sEarth and Ashes is told about the patriotic father that struggle with his blind son during the Russia invasion in Afghanistan, while in AtiqRahimi’sA Thousands Room of Dream and Fear delivers a student who exiles form his life because he is chased, he loves someone saves him. Based on the two reference, AtiqRahimi’sThe Patience Stone becomes the best one to analyze accords to men and women problem culturally. RESEARCH METHOD This study is taking one of the Atiq Rahimi’s stories entitled The Patience Stone as the primary source. In case of analyzing this story, library research is used in order to find some theories, which are relevant to the topic. Finally, Mimesis approach will be used in analyzing this story because the topic that will be discussed about the main character’s silent voice as a woman against patriarchy in her social life as the universal truth. In collecting data, this research focuses on analysis and citations. The first step is reading novel. In this step, novel becomes the object of the research. The novel is entitled The Patience Stone, written by Atiq Rahimi. This is to reach the understanding all contents completely with all possibilities both intrinsically and extrinsically. The second is inventorying data. This step is collecting data through noting the quotations related to the statement of the problems and objectives of the study, it is including in words, sentences, and discourse that can represent patriarchy and feminism in Atiq Rahimi’s The Patience Stone. The third is classification data. This step to classify the data based on the statement of the problems including the portrayal patriarchy and the way the Woman posits herself against it. The fourth is tabling the data. It is to simplify reading the data and classify data that is used in the analysis for the readers. Those collected data are continuosly intrepreted to react the statement of the problems. The handling of a technique is a duty to do, it is to keep the analysis not jumping out of the limitation in order to solve the statement of the problems. Furthermore, it is significant to be on familiar terms with the data that it is from the novel entitled The Patience Stone, written in 136 pages plus 4 pages of brief introduction by KhaledHossaeni. It is written by AtiqRahimi with original title of SynguéSabour. Pierre de patience, published with ISBN: 9780701184102, and by Chatto&Windus. It is addressed at Random House, 20 Vauxhall Bridge Road, in London at 7wiv 25a. The book design is created Chatto and Windus group and translated by Polly McLean. On the dark cover, there is laid a stamp of Goncourt Winner 2008. CULTURAL APPROACH The term culture is a description of a particular way of life, which expresses certain meanings and values not only in art and learning but also in institutions and ordinary behavior (Frow, 1996: 8). Frow also states that culture is the way of life and is the meanings and values in that way of life. Therefore, basically a cultural approach is a way to think about a literary text based on the ideas or customs of certain society in which the text is made. According to Stanley Fish, J. Hillis, and Michael Foucault, language helps create what we call objective reality, thus reality is a social construct since it is created from language which is a product of customs produced by certain society. (Bressler, 1999: 264) Each society or culture contains in itself a dominant cultural group which determines that culture’s ideology, its dominant values it sense of right and wrong, and its sense of personal self worth. (Bressler, 1999: 264) Culrural approach is divided into some theories. Those are: Marxism, post colonialism, new historicism, and feminism (Bressler, 1999: 178). As stated above, cultural approach investigates the domination and the dominated groups. Therefore, this approach will be used to analyze Atiq Rahimi’s The Patience Stone and since the dominated group in this novel is women, the theory of feminism will be used for further analysis. Before going deeper to the feminism, it is important to see that feminism that will be used is the feminism from the glasses of Islam. In the West and East alike, feminists were up against home-grown patriarchalist opponents who used sundry means to denigrate feminism and its supporters. In the West, detractors portrayed feminists as man-haters. In the East, enemies branded feminists as agents of cultural subversion and, ironically in so doing ‘colluded’ with westerners in declaring feminism western. (Kynsilehto, 2008: 26). Therefore, what can be integrated from this Islam feminism understanding is the way Islam see the equality between men and women, from the agents of truth about the equality between men and women, not creating women to hate men just to beg an equality as what west feminism says to. This thought is also influence to the way of the culture move by times, Eastern as universal truth sees, is culturally have features of moral, politeness, differences, and those all shape a unity of eastern culture that is very cultural. While, in Western, thought, rationality, and will or dreams becomes the subjects that move them to be better, and it shapes their mind and finally becomes the culture of west, therefore, the freedom of women seems to be radical rather that to grab the equality. PATRIARCHY Patriarchy system is a system that has been rooted in society generally. Erich From asserts that Patriarchy system is where men is fated to dictate/control women, and it rules to all part in the world. (Fromm, 2002: 177). Engels gives different perspective that patriarchy system is begun when human have already understood about privacy owning, and it marks the birth of system of class. (Budiman, 1981: 21). What Engels means, must reflect to the birth of system of class of men and women. To add it, to make the establishment of this system of men, chronologically there are some experts that give distance between men and women where men are supposed to be the better one.Classically, women are inequality creature, and it is added by Aristotle who views women as an imperfectness of nature (Beauvoir, 2003:ix). Francis Bacon comments that the more negative assertion that women are the jail of men because women give bad effect or influence to men (Arivia, 2002:40). Kant even says that women does not have any ability to use their cognitive ability therefore women should not be allowed to deliver what they think (Arivia, 2002:40). While, St. Thomas supposes women as “imperfect men”, women are creature who are created not deliberately, and it is proven by the symbolic story where Eve is portrayed by Bossuet as a creature who is made of the “Adam’s Rib” (Beauvoir, 2003:xi). According to Cixous, the term of men and women pinpoints to the difference of the two where the first term must posit the higher or better meaning, and it is placed by men. Therefore, men are self and women are the Liyan. Women live in men’s world, therefore women are considered as the Liyan for men. (Tong, 2009:292). Based on those facts, society finally construct a system where men dominate the whole contents of social life. J. Douglas (1976: 34) adds that many feminists use the term patriarchy as a generic term for male privilege, supremacy, and domination, referring to their current as well as past forms. The attraction of this usage is readily apparent: first, its rhetorical punch and strongly pejorative connotations; second, its reminder of the tenacity and continuity of male domination. Despite earth-shaking social changes, not the least of which are the women's Movements of the nineteenth and twentieth century, male power remains. These all continuously give a perspective that women are really controlled, handled, and dictated by men particularly in society. The representation of society can be found in family. Family is the crucial institution in society (Millet, 1972: 33) because it can represent to what happens in the society. In a family the women mostly being the victim of oppressed by their husband or brother. Furthermore, feminist knowledge develops and becomes more sophisticated throughout the 1970s; the family comes to be an important object of analysis. In many cases, it is the crucial site of women s oppression, the space where, unheeded by the world outside, women are at the mercy of fathers or husbands; where the law of patriarchy holds its most primitive form (Pilcher&Whelehan, 2004: 44). Engels as quoted by Millet explains that the ideal type of the patriarchal family and the ancestor is the Roman family, whence come both the term and the legal forms and precedents in the west. Engels informed the word familiaas follow: signify the composite ideal of sentimentality and domestic strife in the present day philistine mind. Among the Romans it did not even apply in the beginning to the leading couple and its children, but to the slave alone. Famulus means domestic slave, and familia is the aggregate number of slaves belonging to one man the expression [familia] was invented by the Romans in order to designate a new social organism the head of which had a wife, children and a number of slaves under his paternal authority and according to Roman law, the right of life and death over all of them(Millet, 1972: 123—124). In family, Gough as quoted by Jo, mentions that men and women cooperate through a division of labor based on gender. Child care, household tasks and crafts closely connect with the household, tend to be done by women; war, hunting, and government by men. Besides that, men in general have higher status and authority over the women of their families, although older women may have influence, even some authority, over junior men (Jo, 1984: 84). Therefore, what things can be inferred to those all understandings, are the problem that is faced by women in the society, the society is like the jail of women and it is sourced by thoughts where place men in a good position to control women. This is also what things reflected on AtiqRahimi’sThe Patience Stone that finally makes the main character, the woman, whispers something as the silent voice in the middle of patriarchy system. This reaction potentially can be said as the thing to get attention and sympathy about what happens to women in Afghanistan, and this can be said as the movement of feminism. FEMINISM In general, feminism is the theory of women’s liberation since the intrinsic in all its approaches is the belief that women suffer injustice because of women’s sex (Humm, 1989: 74). From the inequality that exists between both gender, women want to search equality in the society, they start to speak up their voices in the publicarena. Women themselves must articulate who they are and what role they play in the society. Most importantly, they must reject the patriarchal assumption that women are inferior to men. This started the feminist movement. It was started by the reality that male-female relations is a form of power structure in which men dominate women (Thebaud, 1994: 290). From this starting point the feminist believe that existing inequalities between dominant and marginalized groups can and should be removed. In the practive the feminist scholars attempt to examine beliefs and practices from the viewpoint of the “other”, in this case women, treating them as subjects, not merely objects. Based on all general understanding, it is important to sharpen it into the good shape for not going out of the limitation and wasting buss of explanation of the theory. First of all, it is a long discussion of talking about feminism and its complex sources. To maintain the stability of this research that uses feminism as the knife to slice the discourse of patriarchy reflected in AtiqRahimi’s The Patience Stone, thus the first feminism, the main slicer, continuously will be the main point of theory to discuss. The first wave of feminism appeared in the 19th and early 20th centuries, when women’s suffrage was at the pole position of an industrializing world. In other word, it happened at the age of Victorian age. In 1800, women had little control over their lot in life. The average married female gave birth to seven children. Higher education was off-limits. Wealthier women could use limited authority in the domestic scope but possessed no property rights or economic autonomy. Lower-class women toiled alongside men, but the same social and legal restrictions applied to this stratum of society as well. Somewhat ironically, religion fueled some of the initial social advancements women made at the beginning of the 19th century. The Second Great Awakening, which started in 1790, emphasized emotional experience over dogma, allowing women more leadership opportunities outside of the home. Abolition and temperance movements that shared Protestant undercurrents activated women as well. It is like to what Stuurman, as quoted by Bryson, says that feminist theological arguments were further elaborated in the seventeenth century: for example, some writers used the creation story to argue that Eve was superior to Adam because she wascreated last, or because she was created out of Adam’s rib rather than out of mud and slime (Bryson, 2003: 6). Thus, it can be seen, that in religion, or theologically, the inequality women have, has been rooting to put them down under the knee of men. That means, men are taking higher position in human life where men and women separate them. To talk about the theologically term about the inequality, then women want to get the equality, means that women have something different from the way theology thinks about it and the way of thought is Cartesian with all rationality to think. Bryson notes that the inspiration for these new ways of thinking (feminisms) was the revolution in western philosophy, which had been started in the first half of the seventeenth century by Descartes. According to Cartesian philosophy, all people possess reason, and true knowledge, which is based on experience and self-discovery rather than study of the classics or sacred texts, is in principle available to all. This means that traditional authority is rejected in favor of rational analysis and independent thought, and that customs and institutions which are not in accordance with reason should be rejected. (Bryson, 2003: 6). Therefore, what has been done by feminist is breaking the old thought that is sourced by the empirical way of theology. Moreover, what becomes the main point of this born is the equality that is thought as the right that has been robbed by men and their all system. The first-wave of feminism began in the United Kingdom and the United States around the nineteenth century and lasted until the early twentieth century. The focus of this movement at this time was on de jure inequalities, or officially mandated inequalities. There were many people during this time who were considered to be feminists, Mary Wollstonecraft, Susan B. Anthony, Lucy Stone, Olympia Brown, and Helen Pitts; there are countless more. The first-wave of feminism was monumental to the movement, however, without the continuing second-wave, there would be no hope for feminism in current times, for each wave is connected and dependent on the other's history. In simpler words, feminism is not some simple thing that people can generalize, like it is just an excuse for women to kick men in the balls, and not take care of themselves, or that men and women must be equal at all costs. Feminism is a movement, which has been incredibly important to the success and failures of this country and has been a necessary journey for the women in our country to travel upon so that they can discover and create their own unique place in society. First wave feminists spent hundreds of years in activism, writing, protesting and working for the betterment and equality of their sex and gender. First wave feminists worked not only for suffrage, or the right to vote, but also for the right to an education, the right to work, the right to work safely, the right to the money they earned when they worked, the right to a divorce, the right to their children and the right to themselves and their own bodies. Rights for women can be traced back to the Middle Ages in the Middle East when early reforms under Islam gave women greater rights in marriage, divorce and inheritance. Women in other cultures were not afforded such rights until centuries later. Further improvements of the status of Arab women included things such as the prohibition of female infanticide and recognizing women’s full personhood. The things mentioned above are necessary and were necessary, and in some case, came at the end of long efforts. First wave feminists had to work against this impression, and they had to work against the society that allowed an unmarried woman to be property of her father and a married woman to be property of her husband. The first wave of feminism was the longest, and it is the most taken for granted. It is common now to speak with women who do not identify as feminists who think that feminism is a dirty word, who simultaneously pursue careers and an education, who exercise their right to vote, who own property and benefit from the fruits of their labor. Understanding the history and the efforts of feminism, understanding how much progress they made and how long it took them is important both to those who think they are not feminists, and those who identify as feminists and who live life trying to better the world by the feminist ideal. (Retrieved from uic.edu and pacificu.edu). Victorian feminism is a difficult concept to analyze. On the one hand, some of the greatest reforms of women’s social and legal position before those of the late twentieth century occurred in a few decades of the nineteenth century; on the other, many of those women who were active campaigners—Caroline Norton, Florence Nightingale, Emily Davies, and Barbara Bodichon—were ambivalent about the extent of their own feminism, and over-anxious to distance themselves from unconventional lifestyles and behavior. Moreover, they seemed concerned mainly with the plight of intelligent middle-class single women. Their commitment to respectability gave them something of a timorous or half-hearted allegiance to a more wide-ranging kind of feminism; in any case, their contribution to the feminist cause was often narrowly specialized as they concentrated on a particular campaign—whether for women’s colleges at Cambridge or child custody rights—to the exclusion of others, and many still relied on men to help them with the legal or parliamentary part of their activism. For some, however, it was impossible to avoid being drawn into a wider examination of women’s rights, as happened with Caroline Norton and Harriet Martineau, for example, and by the end of the century, most of the major journals were carrying heated debates about the unsatisfied needs of the modern woman. Beginning initially with spasmodic bursts of activism, first wave feminism gathered pace through the work of specific individuals working for specific ends, until the momentum of events made concern for women’s full participation in social and political life a matter of public interest across the whole political spectrum. This in itself was no mean achievement (Gamble, 2006: 24). According to those all explanations about first wave feminism, that is majorly from west, then it is continued to see this based on the glasses of Islam feminism reflected to AtiqRahimi’sThe Patience Stone. There is a woman that faces a fact of patriarchy system, she cannot do anything except confessing something about the inequality that indirectly getting sympathy for anyone who read to pay the pity about equality of thee Woman should have. The equality is something has been robbed by the patriarchy system, and the way the Woman acts, can be said as feminist movement. As Muslim, this thought can be clearly is seen as east feminist movement. It is like to what Kynsilheto says that it was in this context that some of us reported that Muslim women were subverting the patriarchal Islamist project through what appeared to be a new form of feminism-in-the-making which Muslim women in different parts of the world would soon call Islamic feminism. (Kynsilehto, 2008: 26). Therefore, the understanding of this feminism toward this research goes clearer to see as the relevant theory that will be used to slice the data just to become a good shape of analysis without going out of the limitation. STATUS WOMEN IN AFGHANISTAN The position of women in Afghanistan traditionally has been inferiorto that of men. This position has been continuing to age, socio-culturalnorms, and ethnicity. In fact, Afghan women, even until the beginning of 20thcentury are still being the slaves of their father, husband, father-in-law, and elder brother. Thus, it can be said that the status of women are silence and obedience. The essence of attitude towards women could be clearly seen in the relationshipof the family after the birth of a female baby.The birth of a female baby,particularly in those cases where the mother gives birth to several girls, is the main cause of contracting a second marriage, and it is still happened until nowadays. Girls areusually raised to be good mothers and tolerant housewives. Thus no one pays attention to their education, except in very rare cases in some well-to-do families. Furthermore, they are married to young and even to very old men, in most caseswealthy ones between the ages of 13 and 16, and in certain cases between the ages of 10 and 12, if their parents desire. They were exchanged for what is called “Toyana” or marriage price. Young girls had no right to choose theirfuture husbands, or question their engagement, which is arranged by theirparents. Early marriage is the main cause of suffering for girls in Afghansociety. Such marriages are both physically and psychologically unhealthy,and often resulted in sickness and psycho-neurotic diseases. Many youngmothers pass away during releasing it because of physiological reasons and earlymotherhood.Divorce is an easy act if the husband wants it. Afghan women do not have any right to ask for divorce. The man is the governor, the controller, the dictator, of every authorizing in divorcing. It is a slur for both families.Occasionally, wives were deprived of their rights and claims on their ownchildren. Traditional women refer to their husbands as